Narrativas Sobre Modificaciones en la Comunicación, Jerarquía y Roles en Familias de Hombres que Perdieron el Empleo en la Pandemia (2022)
The present study was carried out under a systemic perspective, with a qualitative theoretical approach, a descriptive methodology and a narrative design, which has as its general objective to describe the narratives about modifications in communication, hierarchy, and roles in families of men who lost the employment because of the pandemic. Four male fathers of families participated, who lost their jobs as a result of the Covid-19 pandemic and who were in that workplace for more than five years. The meanings were obtained by conducting free or unstructured interviews, which were transcribed, for their subsequent interpretation and analysis, from which six categories emerged, three of them emerging